Tactical offensive variables of penalty corner in World Cup men's hockey 2014 - Abd El- Hamid Houta, S. (International Journal of Sports Science and Arts, 2019)
This research aims to Identify the most effective tactical offensive variables while performing the penalty corner in World Cup hockey men's 2014, where the researcher analyzed (272) penalty corner through a form for tactical variables of penalty corner in field hockey which designed by researcher. Research samples were chosen intentionally which include (38) matches for teams that participated in the World Cup of Hockey men 2014, which was held in Netherlands and they were twelve teams. A researcher has used descriptive survey method. The most important results that passing ball by drag is the only used skill in the first pass during ball entrance to the circle in all penalty corners, attackers organization on the circle during penalty corner as two groups is more effective and widely used than one group and finally shooting of the player none receiving the ball using drag flick skill from the right of the goalkeeper is more widely and effectively used than passing the ball in the circle after its fixation and shooting at goal.